Association Between Fissured Tongue and Systemic Diseases: A Contemporary Review - Khaydar Kamilov; Aliya Kadirbaeva; Saodat Musaeva (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Recent studies indicate that fissured tongue may be associated with various systemic disorders, including psoriasis, diabetes mellitus, Down syndrome, and Melkersson–Rosenthal syndrome. The present review summarizes contemporary data regarding the relationship between fissured tongue and systemic pathology. Current evidence suggests that fissured tongue may serve as an important oral marker of underlying systemic disease. Recognition of this condition during routine dental examination may contribute to early diagnosis and comprehensive patient management.